Does the thermal evolution of molecular structures critically affect the magnetic anisotropy?1. Issue 8 (14th August 2015) - Qian, Kang; Baldoví, José J.; Jiang, Shang-Da; Gaita-Ariño, Alejandro; Zhang, Yi-Quan; Overgaard, Jacob; Wang, Bing-Wu; Coronado, Eugenio; Gao, Song
<x xml:space="preserve">Abstract</x> In the absence of a critical phase transition, one can safely use the crystal structure information determined at liquid nitrogen temperature in magnetic anisotropy research.